2016
DOI: 10.1016/j.ebiom.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Temperature on Climate-Sensitive Mortality and Morbidity Outcomes in the Elderly; a Systematic Review and Meta-analysis of Epidemiological Evidence

Abstract: IntroductionClimate change and rapid population ageing are significant public health challenges. Understanding which health problems are affected by temperature is important for preventing heat and cold-related deaths and illnesses, particularly in the elderly. Here we present a systematic review and meta-analysis on the effects of ambient hot and cold temperature (excluding heat/cold wave only studies) on elderly (65 + years) mortality and morbidity.MethodsTime-series or case-crossover studies comprising caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
218
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(284 citation statements)
references
References 25 publications
17
218
1
12
Order By: Relevance
“…Many studies on the similar topic have mainly focused the elderly as a vulnerable subpopulation and called for public interventions for them 34 . Benmarhnia et al 35 identified the need for studies to clarify if young population is also susceptible to extreme temperature in the perspective of public health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the similar topic have mainly focused the elderly as a vulnerable subpopulation and called for public interventions for them 34 . Benmarhnia et al 35 identified the need for studies to clarify if young population is also susceptible to extreme temperature in the perspective of public health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that have investigated high temperature-related respiratory morbidity, there is mounting epidemiologic evidence for a lagged effect of temperature (Bunker et al, 2016; Cheng et al, 2014; Li et al, 2014b; Winquist et al, 2016; Xu et al, 2013; Ye et al, 2012), and several studies have found that the effects of temperature on respiratory morbidity remain after controlling for ambient air pollution (Anderson et al, 2013; Cheng et al, 2014; Li et al, 2014a; Lin et al, 2009; Winquist et al, 2016); these findings suggest a strong, independent effect of high temperature in addition to that potentially mediated through the effect of air pollution. There is less agreement on whether thresholds or non-linear exposure-response functions exist regarding the effects of high temperature on respiratory outcomes (Carreras et al, 2015; Green et al, 2010; Kovats et al, 2004; Li et al, 2014a; Li et al, 2014b; Lin et al, 2009; Michelozzi et al, 2009; Xu et al, 2013), and multi-city studies have reported heterogeneity in the exposure-response function between study locations (Anderson et al, 2013; Michelozzi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bind et al found that air pollution distorts cardiopulmonary risk factors, especially in the elderly males (37). A systematic review and meta-analysis on cause-specific morbidity and mortality related to heat-exposure and cold-stress among elderly conducted by Bunker et al revealed that morbidity and mortality are greater in elderly with diabetes, cardiovascular and respiratory diseases under the heat or cold stress (38).…”
Section: Discussionmentioning
confidence: 99%